坤甸以马内利高中二年级学生汉语学习动机的分析 - Vanisia Vanisia; Wiliyanti Then (Journal of Maobi, 2025)
The purpose of this study is to understand the types of Chinese learning motivation among second-year students at Immanuel Senior High School in Pontianak, as well as the impact of their learning motivation on academic achievement. This research to collect data is employed questionnaires, interviews, and comparative. The data were analyzed using a quantitative approach by organizing the information into tables and relevant statistics with the help of SPSS version 26. Spearman’s rank correlation analysis was applied to examine the relationship between students’ types of Chinese learning motivation and their academic performance. The results show that the students’ primary motivation type is short-term motivation, while external motivation scored the lowest. Furthermore, there is a significant positive correlation between learning motivation and academic achievement, indicating that the stronger the students’ motivation, the better their academic performance.